TalkTutorAI: Empowering English Language Proficiency through ChatGPT-Assisted Conversational Practice – A Case Study at Ubon Ratchathani Rajabhat University, Thailand - Say, Kimchhong; Srisawatsakul, Charnsak; Boontarig, Waransanang (Journal of Applied Informatics and Technology, 2024)
The significance of English as a global language is of growing importance in Thailand, especially in education sectors. However, Thai students often face significant challenges in getting conversational English proficiency. Furthermore, Thailand is classified as a non-English proficient country, showing surprisingly low proficiency levels in English, especially in conversational aspects. Hence, the primary objective of this research is to develop TalkTutorAI, a web application AI chatbot that leverages ChatGPT. TalkTutorAI was designed to positively affect Thai learners by providing a platform to enhance and practice their English language skills efficiently, with the assistance of a powerful AI teacher like ChatGPT. This study employs a design science research approach to address real-world challenges commonly met by Thai learners. The assessment of TalkTutorAI involved 116 student participants from diverse faculties at Ubon Ratchathani Rajabhat University. The evaluation incorporated both testing and survey responses from students, focusing on key factors including user experience, language learning efficiency, content relevance, and overall satisfaction. The results showed a commendable high level of satisfaction with TalkTutorAI, as indicated by an overall experience mean score of 3.82 out of 5, demonstrating a positive reception among participants. Users particularly commended the system for its user-friendly interface and convenience. However, some users suggested improvements, such as enhancing response speed, improving language translation capabilities, and fostering more captivating and human-like interactions. This study suggests that AI chatbots can effectively facilitate English conversation teaching. Furthermore, the findings create a platform for future academic inquiries in this burgeoning domain.